Citation Accuracy in Obstetrics and Gynecology Journals indexed in the Web of Science - Khodabakhshi, Najme; Shekofteh, Maryam; Kazerani, Maryam; Jambarsang, Sara (DESIDOC Journal of Library & Information Technology, 2021)
The accuracy of the citations is crucial in scientific writing. The present study aims to investigate the accuracy of citations in the obstetrics and gynecology journals indexed in the Web of Science. Major and minor citation errors, type of errors, and citation errors in the Q1 to Q4 journals investigate as the objectives. The journals were retrieved by searching the “Obstetrics & Gynecology” category in the Journal Citation Report (JCR) in the Web of Science, and journals in different quartiles (Q1-Q4) were identified by applying the JIF Quartile filter. Eight hundred forty citations were selected from articles in the first five Q1 to Q4 journals using systematic sampling and article type citations were included in the study (730 citations). Bibliographic elements were assessed for citation errors. Findings show that 554 citations (75.89 %) involved errors. Only 24.1 per cent of the citations had no errors. The highest citation errors were related to the volume and issue, with 582 major errors (79.72 %). The citation accuracy in the Q2 and Q3 journals is higher than in other journals. The high rate of citation errors, especially in volumes and numbers, indicates that the journals need to pay attention to citation accuracy in these sections and the use of valid and complete citation styles.